1987
DOI: 10.1071/ch9870599
|View full text |Cite
|
Sign up to set email alerts
|

Variable-Temperature Ultraviolet Photoelectron-Spectroscopy of the Keto-Enol Tautomers of Pentane-2,4-Dione

Abstract: The HeI photoelectron spectra of pentane-2,4-dione measured at various temperatures have been subjected to a spectrum-stripping technique to enable isolation of the complete HeI photoelectron spectra of the keto and enol tautomers. The resulting spectrum-stripping coefficients allow evaluation of the enolization equilibrium constant at each temperature and subsequently the enthalpy of enolization. Interpretation of the photoelectron spectra is achieved with the use of ab initio molecular orbital calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 0 publications
6
37
1
Order By: Relevance
“…The structural analysis has also to take into account the physiological environment in which the compound is placed. Solvent [21][22][23] and phase effects can be critical. For example, an aqueous solution of 2-pyridone contains almost exclusively the amide form (K = 340, [24] ∆G°= 3.4 kcal/mol), whereas in the gas phase the 2-hydroxypyridine form is slightly favored (K = 2.2 [25][26] ∆G°= 0.47 kcal/mol).…”
Section: Introductionmentioning
confidence: 99%
“…The structural analysis has also to take into account the physiological environment in which the compound is placed. Solvent [21][22][23] and phase effects can be critical. For example, an aqueous solution of 2-pyridone contains almost exclusively the amide form (K = 340, [24] ∆G°= 3.4 kcal/mol), whereas in the gas phase the 2-hydroxypyridine form is slightly favored (K = 2.2 [25][26] ∆G°= 0.47 kcal/mol).…”
Section: Introductionmentioning
confidence: 99%
“…13,[16][17][18][19][20][21][22][23][24][25][26][27][28] Both spectroscopic and chemical methods have been used to determine the enthalpy of tautomerization in the gas phase. Unlike the condensed phase studies, agreement between methods is less than satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…[11] The enol content of pentan-2,4-dione was reported to be 95, 68, and 44% at 22, 180, and 275 8C, respectively. [12] This suggested that pentan-2,4-dione acted most likely as a monocarbonyl species in its reaction with PAL at room temperature (20 8C) and, hence, the reaction did not lead to crosslinking for the product to qualify as a hydrogel.…”
Section: Resultsmentioning
confidence: 99%